Efficacy of Abatacept for Arthritis in Patients with an Overlap Syndrome between Rheumatoid Arthritis and Systemic Lupus Erythematosus - Kei Ikeda; Yoshie Sanayama; Sohei Makita; Junichi Hosokawa; Mieko Yamagata; Daiki Nakagomi; Katsuhiko Takabayashi; Hiroshi Nakajima (Clinical and Developmental Immunology)
Introduction. This study aimed to investigate the efficacy of abatacept for arthritis in patients with rhupus, an overlap syndrome between rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Methods. Patients who fulfilled both the 2010 ACR/EULAR criteria for RA classification and the 1997 ACR revised criteria for classification of SLE and received abatacept treatment for arthritis were retrospectively studied. Results. Six rhupus patients who fulfilled the inclusion criteria above were identified. All patients had active arthritis despite receiving antirheumatic drugs including methotrexate when abatacept was initiated. Clinical Disease Activity Index (CDAI) significantly decreased between baseline and 12 weeks () and remained low through 24 weeks. All patients achieved either a good or moderate response according to the EULAR response criteria at 24 weeks. Health Assessment Questionnaire-Disability Index (HAQ-DI) also significantly decreased between baseline and 24 weeks (). In addition, the levels of immunoglobulin G and anti-DNA antibody significantly decreased between baseline and 24 weeks ( and , resp.). Conclusions. Treatment with abatacept is likely to be efficacious in patients with rhupus whose arthritis is refractory to methotrexate. In addition, abatacept may have a moderate effect on abnormal antibody production in rhupus patients.